2014
DOI: 10.1016/j.jval.2014.08.1079
|View full text |Cite
|
Sign up to set email alerts
|

A Payers Perspective to Pharmaceutical Market Access: Defining Market Access

Abstract: Objectives: The aim of the study is to analyze the burden of chronic diseases on public health care expenditures using pharmaceutical data regarding about 2 million individuals. MethOds: Data come from the administrative database of the third Belgian health insurance funds. Without explicit diagnoses of diseases in the database, chronic diseases are mainly estimated using drugs prescription (reimbursed medications only) for a treatment of at least 90 days/year. A multivariate linear model based on the OLS meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Within the research literature, Sendyona and colleagues [ 10 , 11 , 12 ] defined MA as the process that guarantees the development and commercial availability of pharmaceutical products with appropriate value propositions, resulting in their prescription and successful uptake decisions by payers and patients with the ultimate goal of achieving profitability and the best patient outcomes. Still, these authors concluded that “the concept of MA is still poorly understood, and the definition varies depending on the stakeholders’ perspectives” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the research literature, Sendyona and colleagues [ 10 , 11 , 12 ] defined MA as the process that guarantees the development and commercial availability of pharmaceutical products with appropriate value propositions, resulting in their prescription and successful uptake decisions by payers and patients with the ultimate goal of achieving profitability and the best patient outcomes. Still, these authors concluded that “the concept of MA is still poorly understood, and the definition varies depending on the stakeholders’ perspectives” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%